(untitled) (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Passage of meconium in the amniotic fluid during labor has long been considered as fetal compromise resulting from fetal hypoxia or increased vagal activity from cord compression. It is also a sign of normal gastrointestinal tract maturation under neuronal control. However, presence of meconium in the amniotic fluid is traditionally viewed as unfavorable perinatal outcome. So, the present study was contemplated to find the association between grade of meconium during labor and perinatal outcome. Methods: The present prospective study was conducted in the North Bengal Medical College, Sirajganj between January 2016 – April 2017. Based on predefined criteria, 53 singleton pregnant women with meconium-stained liquor (MSL) on spontaneous or artificial rupture of membrane after 37 completed weeks of gestation were included in the study. Meconium-stained liquor was graded as “Thick” if the fluid was dark green in colour, viscous, tenacious, opalescent or opaque containing large amount of particulate materials and “Thin” if the fluid was translucent, light yellow green in colour without particulate material. The perinatal outcome was evaluated in terms of APGAR score of neonates at 1 and at 5 minutes of birth, NICU admission, resuscitation needed, jaundice and respiratory distress syndrome (RDS) due to meconium aspiration. Asphyxia neonatorum was diagnosed if APGAR at birth and/or at 5 minutes was < 7. All the outcomes were then compared between mothers forming ‘Thick’ and ‘Thin’ meconium cohort. Result: Of the 53 meconium-stained liquor, nearly half (49%) was with ‘Thick’ meconium and the half (51%) was with ‘Thin’ meconium. Approximately 85% of the neonates were delivered by lower uterine caesarean section (LUCS) and 80% of the neonates were asphyxiated at birth which reduced to 15.1% at 5 minutes. More than three-quarters (75.5%) of the neonates required resuscitation and 28.3% had respiratory distress syndrome (RDS). The incidences of asphyxia neonatorum, resuscitation needed and RDS were significantly higher in ‘Thick’ meconium cohort than those in ‘Thin’ meconium cohort with risks of having these conditions in the former cohort being 6(95% CI = 1.1–31.2), 4.5(95% CI = 1.1–18.9) and 4.2(95% CI = 1.1–15.7) times higher respectively than those in the latter cohort (p = 0.021, p = 0.031 and p = 0.026 respectively). Conclusion: Majority of the neonates born of mothers with thick meconium cohort are asphyxiated, need resuscitation and/or develop RDS. Asphyxia neonatorum, need for resuscitation and RDS are significantly higher in ‘Thick’ meconium cohort than those in ‘Thin’ meconium cohort with risks of having these conditions in the former cohort being several times higher than those in the latter cohort. Ibrahim Card Med J 2019; 9 (1&2): 67-73